Comparative Evaluation of Dental Imaging Software in Gharyan and Tripoli Dental Clinics - Asma Alnkaa; Hunida Ahqafaf (AlQalam Journal of Medical and Applied Sciences, 2025)
Dental imaging systems are essential tools in modern dentistry, providing accurate diagnostic information and supporting effective treatment planning. In Libya, the availability and performance of these systems vary between regions, creating differences in diagnostic quality and clinical outcomes. This study aims to compare the most commonly used dental imaging devices and software in Gharyan and Tripoli dental clinics—specifically Vatech, Woodpecker, Nanopex, Candy, and V Sensor—by evaluating image quality, usability, reliability, technical support, and overall practitioner satisfaction. A structured questionnaire was distributed to dentists working in public and private clinics in Gharyan and Tripoli. The questionnaire assessed system performance, ease of use, image resolution, affordability, compatibility with clinic infrastructure, and availability of maintenance and technical support. The findings revealed significant differences in the adoption and performance of dental imaging systems between the two cities. Candy35% and Woodpecker25% were the most preferred systems due to their user-friendliness, high-quality imaging, and reliable technical support. In contrast, Nanopex20%, Vatech10% and V Sensor10% received lower satisfaction scores due to limited features and compatibility issues. Overall, practitioner satisfaction was higher in Tripoli, reflecting better access to modern devices and maintenance services. The study highlights the need to standardize dental imaging technologies across Libyan clinics and improve access to high-quality systems, training, and technical support. Enhancing software performance and system integration can significantly improve diagnostic accuracy